Water and Sewer Rates in Minnesota - Gardner, Richard L.; Waelti, John J. (Water Resources Research Center, University of Minnesota, 1977)
This publication summarizes the results of a survey of water and sewer rates in the State of Minnesota. Typical monthly water and sewer bills were computed for small, medium and large municipalities. Summaries were made of the frequency of various rates forms for various sizes of municipalities. Individual water and sewer rates are given for those municipalities responding to the survey.
Keywords: water and sewer rates; water and sewer pricing; minnesota